Discrediting the Dutch: A French Account of the Year of Disaster for Arab Audiences - Baars, Rosanne; van den Bent, Josephine (Early Modern Low Countries, 2020)
Recent historiography has demonstrated how Istanbul became part of a European media landscape in the seventeenth century. This article argues that European countries not only targeted the Ottoman Porte but also tried to reach Arabic-speaking audiences in other major Ottoman cities, such as Aleppo. It does so through an analysis of a remarkable source, an Arabic manuscript pamphlet written by a Frenchman in Aleppo in January 1673, which tells the story of the exploits of Louis XIV in the Dutch Republic during the Year of Disaster. The article will demonstrate the ways in which the French author attempted to discredit the Dutch in the eyes of the inhabitants of Aleppo. An attached Arabic translation of a Neolatin political fable in verse shows the way by which the author imported a European discourse and a European way of influencing audiences to seventeenth-century Syria. The French saw benefits in expanding their ‘image battle’ into the Ottoman Empire and made a conscious attempt to make their propaganda as effective as possible. By studying this pamphlet, we can also further our understanding of the way early modern pamphleteers considered their audiences.